Alveolar Soft-Part Sarcoma: A Case Report: Mexico Hospital, San Jose, Costa Rica - Rojas Vigott, Raquel (2017)
Alveolar soft-part sarcoma is a rare malignant entity with poor prognosis. Chemotherapy has limited activity in this type of sarcoma, we describe here the outcomes of the first case documented in our Institution with metastatic disease, treated exclusively with sunitinib.